If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 4x + -1 Reorder the terms: 3x = -1 + 4x Solving 3x = -1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3x + -4x = -1 + 4x + -4x Combine like terms: 3x + -4x = -1x -1x = -1 + 4x + -4x Combine like terms: 4x + -4x = 0 -1x = -1 + 0 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 2x=2-3x | | (4Y^3-2Y^2)+(7Y^2+3Y-y)= | | 7.4x+51.8=103.6 | | 9AB^2+8AB^2= | | 4x-17+6x-28=15 | | 6m=26 | | 9AB^2-8AB^2= | | 5(2x+3)=6(x-1)+4x | | 50(x-5)=30(x+5) | | 8+4x=9x | | 2x+5=-(2+3x) | | 3p+4=-10p-8 | | 8(2x+3)=4(4x+6) | | -12x=-9x+21 | | 3x^2-54x+241=0 | | 3(x-3)+2(2x)=5 | | 9w=-4w-52 | | 5(2z-3)=15 | | 10y=8y+12 | | 3u-15=7(u-5) | | 2(4x-7)+6=3(5x+2)+7x | | 5x(8+7)+7= | | .2x+.5(12-x)=3.6 | | 8p-6=50 | | 27=5x+3 | | -12=-s | | 3x=5x+3 | | -z=-10 | | 10x-3=8x+9 | | 2(x-4)+8=3x-3 | | 40-12+3x-14+x=18 | | 3y+10+8=-8 |